1992
DOI: 10.1093/bja/68.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Attenuates Sympathoadrenal Responses to Tracheal Intubation and Reduces the Need for Thiopentone and Peroperative Fentanyl

Abstract: The effects of the new, highly selective alpha 2-adrenergic agonist, dexmedetomidine, were studied in a randomized, placebo-controlled, double-blind trial in 24 ASA I patients. Dexmedetomidine 0.6 micrograms kg-1 or saline was given i.v. 10 min before induction of anaesthesia. The required dose of thiopentone was significantly (P less than 0.001) smaller in the dexmedetomidine group (mean 4.4 (sd 0.9) mg kg-1) than in the control group (6.9 (1.6) mg kg-1), and the drug attenuated the cardiovascular responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
192
1
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(212 citation statements)
references
References 31 publications
13
192
1
6
Order By: Relevance
“…Scheinin et al (22) found a close correlation between plasma noradrenaline concentration and the QTc interval. In the present study, QT and QTc durations were increased compared with basal values during laryngoscopy and in the various phases of the post-intubation period in the groups.…”
Section: Discussionmentioning
confidence: 94%
“…Scheinin et al (22) found a close correlation between plasma noradrenaline concentration and the QTc interval. In the present study, QT and QTc durations were increased compared with basal values during laryngoscopy and in the various phases of the post-intubation period in the groups.…”
Section: Discussionmentioning
confidence: 94%
“…Aho and colleagues [138] reported that the administration of an infusion of dexmedetomidine in patients undergoing abdominal hysterectomy was able to reduce isoflurane requirements by 90%. Dexmedetomidine has also been reported to be opioid-and barbiturate sparing [139].…”
Section: Anaesthetic Requirementsmentioning
confidence: 99%
“…13 General anaesthesia was induced by the use of fentanyl 1 mcg/kg and propofol 1.5-2 mg/kg, inj. vecuronium 0.1 mg/kg was used to facilitate endotracheal intubation.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…However, Group D demonstrated more stable haemodynamic changes during the emergence period compared with Group C (Bonferroni corrected P<0.05). 17,13,15 During the operation, ephedrine was administered to seven patients in Group D and four patients in Group C (P=0.338), while esmolol was administered to six patients in Group C and no patients in Group D (P=0.027). No patient in either group experienced bradycardia.…”
Section: Figurementioning
confidence: 99%